Increasing the reach of snowball sampling: The impact of fixed versus lottery incentives - Vashistha, Aditya; Cutrell, Ed; Thies, Bill and (ACM - Association for Computing Machinery, 2015)
Though many researchers have studied how to incentivize people to respond to surveys, little is known about how these incentives impact respondents’ willingness to recruit others to participate as well. In this paper, we show that the incentives offered for individual survey responses can have a dramatic impact on the overall reach of a survey through a network of peers. In a field experiment in India, we made a survey accessible via mobile phones and offered respondents either a fixed incentive (guaranteed payment of about 17). When asked to choose, a significant fraction of respondents preferred the lottery incentive. However, when encouraged to spread the survey, the fixed incentive spread over 100 times further, reaching about 800 people in a day. We interpret this surprising result and discuss the implications for HCI.